2009
DOI: 10.1080/08995600903206362
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in the U.S. Navy: Impact on Performance and Career Continuance

Abstract: Previous research has shown the importance of quality of life (QOL) for critical organizational outcomes such as the retention of U.S. Navy personnel (Wilcove, Schwerin, & Wolosin, 2003) and Marines (Hindelang, Schwerin, & Farmer, 2004). These studies employed a life domains approach addressing a full range of work and non-work life needs as well as specific aspects of each life domain. In contrast, most other research exploring outcomes critical to military organizations focused only on work life needs of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, when PHRM are perceived negatively and as without value by employees, they feel insecure and begin to entertain thoughts of quitting the job. ETI arise because PHRM can generate outcomes such as low salaries, work overload, relocation, layoffs and job dissatisfaction (Wilcove et al, 2009;Dechawatanapaisal, 2017). Thus, when PHRM are not viewed positively by employees, they may begin to entertain thoughts of leaving the organisation.…”
Section: Phrm and Etimentioning
confidence: 99%
“…On the other hand, when PHRM are perceived negatively and as without value by employees, they feel insecure and begin to entertain thoughts of quitting the job. ETI arise because PHRM can generate outcomes such as low salaries, work overload, relocation, layoffs and job dissatisfaction (Wilcove et al, 2009;Dechawatanapaisal, 2017). Thus, when PHRM are not viewed positively by employees, they may begin to entertain thoughts of leaving the organisation.…”
Section: Phrm and Etimentioning
confidence: 99%
“…Later data from the 2002 Navy Quality of Life survey showed that enlisted sailors were dissatisfied with personnel storage space (69%), room in the berthing compartment (66%), rack space (65%), privacy (63%), mattresses (54%), and the berthing area (52%; Wilcove, 2006). Wilcove et al (2003) used data from the Navy Quality of Life survey to show that satisfaction with shipboard life (to include habitability factors) was associated with personnel intention to reenlist, career continuance plans, and job performance (Wilcove et al, 2009). In 2008, Wilcove and Schwerin (2008) showed that conditions in the berthing compartments and privacy were negatively associated with crew retention.…”
Section: Introductionmentioning
confidence: 99%
“…The intersection of habitability and behavioral health functioning in operational environments has long been recognized as essential for enhancing mission success and crew performance (Amick & Russi-Vigoya, 2020;Kearney, 2016aKearney, , 2016bMatsangas & Shattuck, 2020;Wilcove, 2006;Wilcove et al, 2003Wilcove et al, , 2009. In order to systematically contribute to an empirical foundation for recommended thresholds of vehicle/habitat designs for longduration missions, it is critical to have an instrument capable of assessing behavioral health and performance-relevant outcomes over time in operational environments.…”
Section: Discussionmentioning
confidence: 99%